Involuntary Unemployment in Dynamic Contract Equilibria. - MacLeod, W; Malcomson, J (Department of Economics (Queen's University), 1986)
In this paper the set of bilateral wage contracts in a dynamic model with observable effort is characterized. Our first result demonstrates that bond payments and severance pay do not increase the size of the set of incentive compatible contracts. Second, we show that unobservable effort can lead to voluntary unemployment.